Re-Reading Al-Uqud Al-Murakkabah: Types and Models of Hybrid Contracts Concept in Fatwa DSN-MUI - Pitriani Pitriani; Doli Witro; Muhamad Izazi Nurjaman; Iib Hibaturohman; Imaro Sidqi (Khazanah Hukum, 2024)
The aims of this research is to clarify the type of multi-contract used by National Sharia Council-Indonesian Ulama Council (DSN-MUI) in its product innovation, so that the multi-contract concept used is a multi-contract concept that is in accordance with sharia rules and principles. This research is sharia economic law research that uses descriptive literature research methods. This research uses a normative juridical approach. The primary data used in this research is the DSN-MUI Fatwa which is related to the concept of hybrid contracts in the innovation of sharia banking products. Meanwhile, Secondary data sources include various sources of literature such as laws, scientific articles, books, and others. The data analysis technique used was the cumulative data analysis technique of Miles et al., namely data condensation, data presentation, and drawing conclusions. This study found that so far, the DSN-MUI has used the type of multi-contract for similar contracts (a combination of muawadhat contracts) and also non-similar contracts (a combination of muawadhat contracts and tabarru’ contracts) provided that there is a separation of agreement documents to avoid usury schemes for the use of these contract combinations and income (both margins, ujrah, and profit sharing) is obtained from the use of muawadhat contracts. This non-similar contract combination scheme is confirmed in the Fatwa on the Income of Islamic Financial Institutions (LKS) During the Construction Period (Fatwa No. 142 of 2021), namely Al- Uqud al-Murakkabah al-Muta’addidah. Meanwhile, the hybrid contracts scheme for similar contracts uses the Al-Uqud al-Murakkabah al-Mutajanisah hybrid contracts scheme